RELATIONSHIP BETWEEN STOCK MARKET RETURNS AND EXCHANGERATES IN EMERGING STOCK MARKETS - Arshad, M.N.; Yahya, M.H. (IKONOMIKA, 2016)
Abstract-This paper aims to study the relationship between stock market returns and exchange rates in emerging stock markets including Malaysia, Singapore, Thailand, Indonesia and Philippines. The data is taken from January 2003 to December 2012 using weekly closing indices and separated in two periods; before (2003-2007) and second, after (2008-2012) the financial crisis of 2008. Johansen-Juselius (JJ). Granger causality tests show that unidirectional causality exists between the stock market returns and exchange rates for Thailand before the financial crisis, whilst, for Indonesia and Singapore, the unidirectional causality between the two variables is detected in the period after the financial crisis. Error Correction Model (ECM) indicates the existence of long run causality between the two variables for Philippines. This study also finds that most of the emerging stock markets are informationally inefficient.